2017
DOI: 10.1111/ijn.12598
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and associations of sickness presenteeism and sickness absenteeism in nurses: A systematic review

Abstract: The ability to predict presenteeism and absenteeism in nursing is useful to constrain costs and ensure that quality care is delivered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
81
1
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 54 publications
(219 reference statements)
6
81
1
8
Order By: Relevance
“…Contrary to respondents’ view that absenteeism is more common on Fridays and Mondays, the statistics revealed Wednesdays and Thursdays as the days with higher incidence of absenteeism. Weekends saw the lowest absenteeism rates, possibly due to the financial incentive given for working during weekends, or fear of losing this income, as well as the availability of family members to care for children (Brborovic, Daka, Dakaj, & Brborovic, ). However, lower absenteeism during weekend days may shift absenteeism to weekdays, and mid‐week absenteeism may perhaps be fatigue related.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to respondents’ view that absenteeism is more common on Fridays and Mondays, the statistics revealed Wednesdays and Thursdays as the days with higher incidence of absenteeism. Weekends saw the lowest absenteeism rates, possibly due to the financial incentive given for working during weekends, or fear of losing this income, as well as the availability of family members to care for children (Brborovic, Daka, Dakaj, & Brborovic, ). However, lower absenteeism during weekend days may shift absenteeism to weekdays, and mid‐week absenteeism may perhaps be fatigue related.…”
Section: Discussionmentioning
confidence: 99%
“…Weekends saw the lowest absenteeism rates, possibly due to the financial incentive given for working during weekends, or fear of losing this income, as well as the availability of family members to care for children (Brborovic, Daka, Dakaj, & Brborovic, 2017). However, lower absenteeism during weekend days may shift absenteeism to weekdays, and mid-week absenteeism may perhaps be fatigue related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presenteeism rates due to both sickness and job‐stress in nursing are higher than rates in other job sectors (e.g., finance) (Aronsson, Gustafsson, & Dallner, ; Rainbow, Gilbreath, & Steege, ). Previous studies of nurse presenteeism have focused on quantifying the prevalence and consequences of presenteeism (Brborović, Daka, Dakaj, & Brborović, ; Letvak et al, ). However, nurses have not previously been asked to explain in their own words what would contribute to their presenteeism and what they believe are the related consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies focused on factors specifically related to the professional role of health care personnel and on replacement difficulties (ie, impact of perceptions on how easily missed work due to sickness absence could be made up for) that may explain relatively high rates of sickness presence in these occupations. More recently, a systematic review of presenteeism among health care employees has revealed that a wider variety of explanatory factors can contribute to the prevalence of presenteeism, such as psychosocial working conditions, employment conditions, and conditions related to sickness insurance . According to a Dutch study, there was also an indication that job demands and burnout exhibited a substantial longitudinal relationship with presenteeism among nurses …”
Section: Introductionmentioning
confidence: 99%